2019
DOI: 10.1080/19336950.2019.1631107
|View full text |Cite
|
Sign up to set email alerts
|

The role of oligodendrocyte gap junctions in neuroinflammation

Abstract: Gap junctions (GJs) provide channels for direct cell-to-cell connectivity serving the homeostasis in several organs of vertebrates including the central (CNS) and peripheral (PNS) nervous systems. GJs are composed of connexins (Cx), which show a highly distinct cellular and subcellular expression pattern. Oligodendrocytes, the myelinating cells of the CNS, are characterized by extensive GJ connectivity with each other as well as with astrocytes. The main oligodendrocyte connexins forming these GJ channels are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 129 publications
(234 reference statements)
0
27
0
Order By: Relevance
“…Among these Cxs on oligodendrocytes, Cx47 participates in the formation of gap junctions with astrocytic Cx43 (19). Recently, studies have revealed that astrocyte-oligodendrocyte gap junctions are essential for CNS myelination and homeostasis (71). Some studies have found that astrocytes can deliver glucose and lactate to oligodendrocytes through gap junctions, which is essential for the survival of neuronal axons (72,73).…”
Section: The Neuron-glial Syncytium Structure In the Central Nervous mentioning
confidence: 99%
See 1 more Smart Citation
“…Among these Cxs on oligodendrocytes, Cx47 participates in the formation of gap junctions with astrocytic Cx43 (19). Recently, studies have revealed that astrocyte-oligodendrocyte gap junctions are essential for CNS myelination and homeostasis (71). Some studies have found that astrocytes can deliver glucose and lactate to oligodendrocytes through gap junctions, which is essential for the survival of neuronal axons (72,73).…”
Section: The Neuron-glial Syncytium Structure In the Central Nervous mentioning
confidence: 99%
“…Studies have reported that the existence of astrocytic Cx43 is necessary for the functions of oligodendrocytes (71,131). The loss of astrocytic Cx43, which forms hemichannels and gap junction channels on the astrocytic membrane, could disrupt the Cx43/Cx47 gap junctions, which are harmful for the transmission of ions and nutrients between astrocytes and oligodendrocytes (132).…”
Section: Functions Of Astrocyte-oligodendrocyte Couplingmentioning
confidence: 99%
“…Disruption of oligodendrocytes from each other and from astrocytes, i.e. deconstruction of pan-glial network, has been observed in experimental models of demyelination (unpublished data) and frequently reported in MS and neuromyelitis optica (41,(57)(58)(59). Mutations in Cx47 and Cx32 result in developmental CNS and PNS abnormalities in leukodystrophies (60,61).…”
Section: Discussionmentioning
confidence: 81%
“…To validate the presence of glial-glial interactions, we investigated whether the grafted hiOLderived progeny had the machinery to be connected to one another via gap junctions. To this end, we focused on oligodendrocyte-specific Cx47 and astrocyte-specific Cx43 as Cx43/47 channels, which are important for astrocyte/oligodendrocyte cross talk during myelination and demyelination (40,41). Combined immunolabeling for hNOGOA, CC1, OLIG2 and Cx47 revealed that MS-derived oligodendrocyte cell bodies and processes were decorated by Cx47+ gap junction plaques, that were often shared by exogenous MS-derived oligodendrocytes or by MS and endogenous murine oligodendrocytes ( Fig.…”
Section: Ms-and Control-hiol Progeny Functionally Connect To Other Glmentioning
confidence: 99%
“…As far as we are now aware, besides being part of glial cells, oligodendrocytes do not have a major role in the physiological neuroinflammation, since they mainly provide physical and metabolic support to neurons promoting the myelinating process [ 6 ]. Noticeably, oligodendrocyte gap junctions’ deficiency due to genetic defects has been associated with increased neuroinflammation in mouse models, indicating that the altered expression of connexins in oligodendrocytes, besides being a consequence of inflammation, can also promote a proinflammatory environment [ 7 ]. Astrocytes are the most numerous glial cells of the CNS, exerting diverse roles, such as the regulation of synaptic plasticity and, more broadly, the control of brain homeostasis, also by coordinating local energy metabolism.…”
Section: Introduction: the Cellular Players Of Neuroinflammationmentioning
confidence: 99%